Aplicación de un protocolo de manejo de masas anexiales: ahorro en actividad clínicamente innecesaria y costes - De Matías Martínez, M.; Noguero Meseguer, M.R.; Cuesta Cuesta, A.B.; Abreu Griego, E.D.; Bartolomé Sotillos, S.; Martín de los Ríos, M.D. (Anales del Sistema Sanitario de Navarra, 2020)
Background. Evaluate whether the implementation of an adnexal masses protocol, based on the GI-RADS system, allows a correct management of these masses, avoiding unnecessary clinical activity produced by overdiagnosis and overtreatment, as well as cost savings. Methods. Retrospective cohort study (July 2015 - June 2017) including women treated at the Gynaecology clinic of the Hospital Universitario Rey Juan Carlos (Móstoles, Madrid), with detection of an adnexal mass in high resolution echography. Adnexal masses were classified by the GI-RADS system, and together with the echographic image and menopausal status, surgery or follow-up was decided. Results. A total of 154 women were studied, 24 % with images suggesting malignancy (G4 and G5). Surgery was performed on 33.1 % of adnexal masses; 33.3 % of them were ovarian carcinoma, mainly (88.2 %) in postmenopausal women with echographic images suggesting malignancy. Three point two percent of patients rejected the recommended surgery. During follow-up 21.4 % of the masses disappeared, 61 patients were only monitored due to a stable mass and two (1.3 %) due to surgical risk. Eventually, 96 (62.3 %) surgeries were avoided, achieving a 57,683 Euro saving. Conclusions. The application of a protocol based on the GI-RADS classification system avoided unnecessary surgeries, as well as the consequences and economical cost produced by them. Thus, this protocol is a useful and practical tool for the monitoring and treatment of adnexal masses.